Political Transformation of the French „National Rally” and Gender Analysis of Party Election Programs - Darbaidze, Eka (Politics / პოლიტიკა, 2020)
The far-right populism in modern world has become more powerful, and Brexit in the UK, the election of Donald Trump as a President of the United States, and the strengthening of ultra-right forces in European countries and the European Parliament is a proof of it. Ultra-right-wing forces are particularly supported in Germany, France, Italy and Hungary. The French National Rally is party that never had so much support in France as in the last national and European elections, in which radical right-wing forces were able to mobilize and support a significant portion of the electorate. The arrival of Marine Le Pen as chairman of the National Front in 2011 gave the party a breath of fresh air and took it to a new level of development. Under Marine Le Pen, the National Rally has managed to modernize some of its conservative positions on gender, sexuality, and family issues. With the new discourse, the leader of the National Rally aims to attract a segment of voters who have traditionally been the least considered among the electorate of the National Rally, and women are among such electorate. The aim of this article is to study and analyze reasons that has caused so much power and support for ultra-right populism in Europe, specifically what factors are contributing to the popularity and support of ultra-right forces among the women voters? How sensitive is the party's policy and how do the National Rally's election platforms respond to the needs and demands of women voters? There is no doubt that the party is actively seeking the goodwill of female voters and mobilizing them around the party, as evidenced by the growing number of female candidates from the National Rally in recent elections and the active support of the female electorate in the presidential election. Despite all this, public organizations working on women's rights in France, feminist activists and their supporters believe that Marine Le Pen is a serious threat for a women's rights and she puts under the question national and regional achievements in the fight for women's rights.
Keywords: radical right-wing parties; National Front; National Rally; Marian Le Pen; ultra-right forces; women voters; women' s rights